ANALISIS SISTEM INFORMASI AKUNTANSI PENERIMAAN KAS DARI JASA REPARASI KAPAL PADA PT. DOK & PERKAPALAN KODJA BAHARI (PERSERO) SHIPYARDBANJARMASIN (Prospect : Jurnal Manajemen dan Akuntansi, 2018)
This study aims to determine the implementation of accounting information system cash receipts from ship repair services at PT. Diving & Shipping Kodja Bahari (Persero) Shipyard Banjarmasin. The study was conducted from 12 November to 17 November 2017. In the research using qualitative descriptive data is a method that provides a systematic description of a state of research by collecting, recording, analyzing data that has been collected. The data collected in the form of: sentence, image and flowchart / system. Data collection techniques used in this study are observation, interview and documentation.The result of the research is that the company already has an organizational structure that separates each function. The document used has been made indupli cate, serial number printed and has been authorized by the authorities. Cashreceipts from reparations services are in accordance with the procedures /systemsthat apply But the cash receipt information system is still there is a lack of the absence of separation of tasks on the accounting department that specificallyhandles the receivables and journal sections. While the cash / part of receipt shouldbe sent to the company account. Because the company implements a non-cash payment system in accordance with the Directors' Decree on financial management mechanisms. All receipt activities, directly received by the Bank. Therefore there is no cash word in terms of acceptance of the repair service.